Determination Of Scientific Argumentation Skills Of Biology (Contribution To Digital Literacy And Critical Thinking Skills Of High School Students) - Nur Khoiri; Faiqotul Wafiqiyah; Darnoto; Budi Cahyono (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
This study aims to describe the relationship between digital literacy and critical thinking skills with high school students' scientific argumentation skills. The sampling technique used purposive sampling. The basis for sampling was an equivalence test usingKruskal Wallis test, which shows that all population classes are not in equal conditions. Therefore, further tests are used to identify class groups that have equal learning outcomes. The techniques used to collect data are test and non-test survey methods. Tests are used to collect research data obtained through critical thinking and scientific argumentation test instruments. Non-test techniques are used to collect questionnaire and interview data. The questionnaire instrument is used to obtain digital literacy data. Data were analyzed using multiple linear regression tests, partial T tests, simultaneous F tests, coefficient of determination tests, and correlation tests. The results of the study show that 1. The relationship between digital literacy and scientific argumentation skills of grade XI high school students is significant with a value of themselves 0.001<0.005 with a negative relationship, 2. The relationship between critical thinking skills and scientific argumentation skills of grade XI high school students is positive and significant with a value of 0.001<0.05, 3. The relationship between digital literacy and critical thinking skills with scientific argumentation skills of grade XI high school students is positive and significant with a value of 0.001<0.05. The contribution of digital literacy and critical thinking skills to scientific argumentation skills is 31.8%, while the remaining 68.2% is influenced by other factors not examined by the researcher.